2007
DOI: 10.1016/j.bbamem.2006.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Coencapsulation of irinotecan and floxuridine into low cholesterol-containing liposomes that coordinate drug release in vivo

Abstract: A liposomal delivery system that coordinates the release of irinotecan and floxuridine in vivo has been developed. The encapsulation of floxuridine was achieved through passive entrapment while irinotecan was actively loaded using a novel copper gluconate/triethanolamine based procedure. Coordinating the release rates of both drugs was achieved by altering the cholesterol content of distearoylphosphatidylcholine (DSPC)/distearoylphosphatidylglycerol (DSPG) based formulations. The liposomal retention of floxuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 26 publications
1
81
0
1
Order By: Relevance
“…In fact, all our binary mixtures are seen to form liposomes when dispersed in water. Liposomes have long been recognized as devices for the slow, sustained release of drugs [13,14]. The fact that the slow release of edelfosine reduces or abolishes haemolysis while keeping almost intact its apoptotic effect suggests that both phenomena occur through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all our binary mixtures are seen to form liposomes when dispersed in water. Liposomes have long been recognized as devices for the slow, sustained release of drugs [13,14]. The fact that the slow release of edelfosine reduces or abolishes haemolysis while keeping almost intact its apoptotic effect suggests that both phenomena occur through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach has emerged as a promising strategy for cancer treatment, there are a limited number of research studies reporting successful drug coloading in the same carrier (Tardi et al, 2009;Zhao et al, 2008;Harasym et al, 2007;Mayer et al, 2006). This is likely the result of technical difficulties associated with the efficient and stable encapsulation of two drugs inside a single carrier as well as challenges in controlling the drug leakage rate and still maintaining the entrapped drug:drug ratio after systemic administration Tardi et al, 2007). There are three different approaches to formulate a drug combination involving liposomal design: i) combination of a liposomal drug with a free drug; ii) encapsulation of two drugs in individual liposomal carriers that are subsequently combined at the desired ratio and iii) co-encapsulation of two drugs in the same carrier by means of a simultaneous or a sequential drug loading.…”
Section: Design Of Liposomal Formulations For Drug Combination Deliverymentioning
confidence: 99%
“…iii. Co-encapsulation of two drugs in the same liposomal carrier seems to be a preferable solution as compared to administration of individual liposomal drugs since it reduces cost production, minimizes lipid load to the patient, which has been associated to infusion-related side effects, and eliminates the potential interference that each liposome population may exert in the pharmacokinetic profile of the other Tardi et al, 2007). Furthermore, co-encapsulation overcomes potential uncertainties about drug biodistribution provided by the different liposome compositions.…”
Section: Design Of Liposomal Formulations For Drug Combination Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that combining either drugs or antigens can result in increased therapeutic effects over monotherapies of immunoliposomal drugs. Co-encapsulation of two different anticancer drugs in the same liposome have recently been described [141][142][143], making it possible to investigate the therapeutic effects of bispecific immunoliposomes coencapsulating a combination of drugs.…”
Section: Combination Of Immunoliposomal Drugsmentioning
confidence: 99%